A correction to the Lepanthes guatemalensis group (Orchidaceae: Pleurothallidinae) in Costa Rica, with a new species - Pupulin, Franco (Phytotaxa, 2021)
The true Lepanthes edwardsii is first recorded for the flora of Costa Rica, described and illustrated on the basis of a Costa Rican voucher. The taxon previously recorded under that name is described as new to science as Lepanthes bogariniana; it is closely related to L. edwardsii, L. durikäensis, and L. viquezii, but can be distinguished by the narrowly elliptic lateral sepals, the tails straight to curved inward, the lobes of the petals with rounded apices, the blades of the lip straight and not bent towards the lateral sepals, and the yellowish-white column.